Jaminan Konstitusionalitas Hak Asal Usul Masyarakat Hukum Adat di Sumatera Barat - Taufik, H. Ilhamdi; Alia, Muhammad Ikhsan (Lex Journal: Kajian Hukum & Keadilan, 2017)
Post-authoritarian Indonesia guaranteed the protection of Indegeneous People are accelerated on behalf of Indonesian Constitution UUD NRI 1945. Coherently, the Constitution obligated the government to emerged an effective and comprehensive regulation to protect traditional ethnic alongside their cultural rigjhts. As the consequences, state obligated all stakeholder included local government to reformulate legal platform as the implementation of UUD 1945 mandate. In the historical and political aspect, existence of in degeneous people is settled long time before the official declaration of state. Indegeneous people not only served as one of prequisite requirement of human rights implementation. However, based on historical context recognition of indegeneous people has been decreased recently. It is caused by the economic development that sometimes impacted the territorial of indegeneous people itself. Furthermore, the assimilation process of indegeneous people and “new-comer” citizen has limited the space for indegeneous people to conduct their ritual as cultural-religious community. The main puzzle to be elaborated in this research are how UUD 1945 maintain the constitutional protection to indegenous people. Secondly, how the implementation of constitutional protection over indegeneous people in Indonesia. This research suggested constructive advices to overcome the problem. Firstly, emerging recognition and protection over indegeneous people through sincronization of state and local government regulation. Secondly, this research urging the government to sttle a legal platform for conflict resolution among indegeneous people and between indegenous people and government.